Glycoside esters from lichens of central Asia - Rezanka, T; Guschina, I A (Phytochemistry, 2001)
Ten compounds isolated from the extract of the central Asian lichens comprised new glycosides and glycoside esters having 18R-hydroxy-dihydroalloprotolichesterinic, 18S-hydroxy-dihydroprotolichesterinic and 18S-hydroxy-neodihydroprotolichesterinic acids, as the aglycones and a saccharide moiety linked at C-18 and also at C-21 made by glucose, xylose or rhamnose. The structures were elucidated using extensive spectroscopic analysis (1D and 2D NMR, MS, IR, UV and ORD) and by biochemical methods.
Keywords: Glycosides; spektrální analýza; Lichens; lišejníky; Esters; Spectrum Analysis; Plant Extracts; estery; rostlinné extrakty; glykosidy